2019
DOI: 10.2533/chimia.2019.395
|View full text |Cite
|
Sign up to set email alerts
|

tRNA Biology in Trypanosomes

Abstract: Besides their medical importance, the parasitic protozoan Trypanosoma brucei and its relatives are experimentally highly accessible model systems for many cell biological processes. Trypanosomes are phylogenetically essentially unrelated to the popular model eukaryotes, such as yeast and animals, and thus show several unique features, many of which are connected to RNA. Here we review the tRNA biology of trypanosomes. Even though tRNAs were already discovered 60 years ago, owing to current technological advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…Moreover, tRNAs appear to be imported as fully processed molecules (11,12). The exclusive reliance on mitochondrial tRNA import has initiated a more general interest in trypanosomal tRNA biology (1). Aminoacyl-tRNA synthetases (aaRSs) have been studied extensively and it was shown that, likely due to mitochondrial tRNA import, most but interestingly not all aaRSs are dually targeted to the cytosol and the mitochondrion (3,(13)(14)(15).…”
mentioning
confidence: 99%
“…Moreover, tRNAs appear to be imported as fully processed molecules (11,12). The exclusive reliance on mitochondrial tRNA import has initiated a more general interest in trypanosomal tRNA biology (1). Aminoacyl-tRNA synthetases (aaRSs) have been studied extensively and it was shown that, likely due to mitochondrial tRNA import, most but interestingly not all aaRSs are dually targeted to the cytosol and the mitochondrion (3,(13)(14)(15).…”
mentioning
confidence: 99%
“…As such it might represent a novel pathway that supports host-parasite interactions and sustains infection. In this context, complementing the pool of tRNAs transcribed by the parasite with the import of specific exogenous/host tRNAs could play a punctual role during the developmental cycle, either by promoting protein synthesis at specific stages or by enabling unrelated signaling processes such as those reviewed in ( 47 , 48 , 49 ). The absence of other examples of import of exogenous tRNAs beyond the Plasmodium genus complicates its characterization but also offers new opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a numerical “2” is appended to the mitochondrial version of the synthetase, for example, in aspartyl tRNA synthetase, the cytosolic form is abbreviated as DRS1 and the mitochondrial form as DRS2. It is noteworthy that unlike other eukaryotes that possess at least two genes for most of the cytosolic and mitochondrial aaRSs, the trypanosomatids encode only one gene except for a few, such as AspRS, TrpRS, and LysRS. , In trypanosomatids, 26 aaRSs have been recognized . In reference to Trypanosoma, a study revealed that alternate trans-splicing of an immature RNA results in formation of isoforms, the one with mitochondria targeting sequence (MTS) is directed toward mitochondria while the one devoid of MTS is retained within cytosol .…”
Section: Aminoacyl Trna Synthetases As Drug Targetmentioning
confidence: 99%